Developing Canva-Assisted Interactive Problem-Based Learning Model to Improve Mathematical Critical Thinking Ability - Hana Cunayah; Heris Hendriana; Galih Dani Septiyan Rahayu ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2026)
The purpose of this study is to find out how to develop a PBL learning model assisted by the Canva Interactive application on fraction material . This type of research uses Research and Development (R&D) using the Borg and Gall model. The sampling technique uses simple random sampling, namely class V (Five) from SDN 1 Hegarmanah totaling 23 students, SDN 3 Mulyamekar totaling 47 students, SDN 2 Cicadas totaling 19 students, and SDN Cilangkap totaling 24 students . Data collection techniques use interviews, observations, Pre-tests and Post-tests (critical thinking skills) . The data analysis test used is qualitative descriptive analysis, which describes the results of product development. The results of the research conducted on the validation test obtained an average score of 4.46 with the criteria "suitable for use without revision " by 2 expert lecturers, 4.7 with the criteria "suitable" by 1 expert teacher. Product trials were conducted on a small and large scale, obtaining an average percentage of independent sample test output based on equal variances assumed for a Sig value (2-tailed) of 0.000 <0.05. Based on this, it can be concluded that H0 is rejected. Meanwhile, the increase in students' critical thinking abilities obtained an average N-Gain percentage of 41.27% with the category of " quite effective ". The results of this study indicate that the PBL model assisted by the Canva Interactive application developed has the criteria of being feasible/valid and is effective enough to be used as a learning tool in mathematics learning.